“Charles Dickens walked past here”: Dickensian Topography and the Idea of Fellowship - Malcolm ANDREWS (E-REA)
The essay explores the idea of Dickensian topography, in relation both to Dickens’s own preoccupation with topographical specificity in the novels and to the practices of literary tourism in “Dickens Country.” It suggests that there is a kind of synergy between the experience of his novels and the confrontation with surviving sites connected with their actions and characters. Dickens himself, as a child, projected the imaginary characters and their adventures from his favourite eighteenth-century novelists onto the real places of his childhood home town of Chatham. In his own writing he mapped fictional events onto named real places, especially in London and Kent, with vivid topographical detailing. Hence arose the idea of a visitable Dickens Country, where Dickens enthusiasts, such as those associated with the Dickens Fellowship organisation, have a sense that they are closing in on the reality of Dickens’s imaginary worlds, and even experiencing a kind of Dickensian presence.